A matemática básica na avaliação de investimento em ações: aplicações e propostas de ensino - Sirtoli, Felippe Carniel (2022)
Considering the new Brazilian curriculum base for education, which introduced the concept of Formative Itineraries, we present in this work a teaching proposal on investments in stocks that can serve as a learning route in Financial Education for students in the last years of High Shcool. Initially, we seek to present to teachers and students the basic concepts and results of Markowitz’s Modern Portfolio Theory applied to the stock market. It starts with assembling an investment portfolio and the weight each financial asset represents within the portfolio, reaching the calculation of return, expected return, and investment risk. In this context, we present proposals for activities structured by level of complexity and involving High School mathematical and statistical content.